A dinâmica do jogo em alguns procedimentos da arte - Marco Antonio Oliveira Mota (2010)
This research is about my own artistic work before theoretic investigations around visual and literary arts. The word-image relations here are an approach made by means of the concept of game and its consequential dislectics, of the relations between spatiality in art and literature and of the descriptive writing. For this I anlyze some 1970s Conceptual Art pieces and the theory raised about it in that time; the activities of Oulipo- a French literary workshop which acts since the 1960s over George Perec1s work and finally the Argentinean artist Jorge Macchis work. Before this and considering that may artistic production includes writing, this work is a poetic reflection about the undertones that give colour to language.